THE PHILOSOPHY OF THE ABSURD IN ALBERT CAMUS - Раджабов Руслан Раджабмуродович; Пулатова Дурдона Лукман кизи (Web of Journals Publishing, 2025)
The article presents the views of researchers on the concept of tragedy. Albert Camus's works raise complex issues related to the absurd. Camus deeply analyzes tragedy in a number of his works related to the philosophy of the absurd and existentialism.
Keywords: Absurdity, existentialism, suicide, tragedy, death, existence, philosophy, society, reflection, indifference.